Assessment of process parameters in a dehumidification process using biomass-based wood shaving as a packing material. Issue 2 (February 2022) - Salins, Sampath Suranjan; Reddy, S. V. Kota; Kumar, Shiva
In the current study, the performance of the counterflow dehumidification test rig using wood shaving packing has been analysed. Wood shaving packing with the density 500 kg/m 3 was used along with the CaCl2 desiccant with varying concentration. Mass flow rate of air was varied and the dehumidification performance parameters like moisture removal rate, dehumidification efficiency, coefficient of performance, change in relative humidity, change in the pressure and mass transfer coefficient were evaluated. Output parameters were compared with the commercially available cellulose packing with the wettability of 632 m 2 /m 3 . Results showed that, even though the performance of wood shaving packing is slightly less than the Celdek packing, performance of wood shaving is promising at 40% desiccant solution concentration. Maximum relative humidity difference, coefficient of performance and dehumidification efficiency obtained with wood shaving pad material were found to be 19%, 1.88 and 69.5%, respectively.